TRADISI WIWITAN - Kajian Simbolik-Hermeneutik terhadap Masyarakat Desa Jetak, Kecamatan Wedung, Demak, Jawa Tengah - Tajrid, Amir (Sabda: Jurnal Kajian Kebudayaan, 2012)
Wiwitan tradition of Jetak villagers, Wedung district, Demak Regency, is a value system in a society which is expressed through symbols. These symbols can be viewed as ritual representation containing confidence, sacrifice and hope of peace, balancing between the physical and the spiritual, and fusion of Hindu-Budha elements and Islamic values. Besides, symbols used in stages and processes of wiwitan tradition were means of expressive communication delivered to mean to convey our hopes to God the Almighty.